The Legal Status of Marriage (Merariq) Implementation Within The Indigenous People of Sasak Lombok - Hariati, Sri; Moh. Jamin; Adi Sulistiyono (Magister of Law, Faculty of Law, University of Mataram, 2024)
This research examines the legal status of merariq marriages within the Sasak traditional community in Lombok. Merarik marriages, governed by customary practices and norms, often conflict with Indonesia's national positive law. This study explores the interaction between Sasak customary law and national law regarding merarik marriages. Using qualitative methods and a case study approach, the researcher conducted in-depth interviews with traditional leaders, legal practitioners, and community members to gain a comprehensive understanding of the issue. The findings reveal a discrepancy between national legal provisions and customary practices, creating challenges in legal recognition and enforcement. The study suggests that harmonization between customary and positive law is necessary to ensure fair recognition of customary practices and the protection of individual rights. This research aims to enhance understanding of the legal dynamics within Indigenous communities and support the development of policies that are inclusive and responsive to cultural diversity.